2007
DOI: 10.1185/030079907x242773
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of open-label donepezil treatment in patients with Alzheimer's disease discontinuing memantine monotherapy

Abstract: Donepezil was effective and well tolerated in moderate-to-severe AD patients who discontinued memantine monotherapy, including those with previous exposure to ChE inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…A 12-week, multicenter, open-label study in 103 patients with moderate-to-severe AD focused on switch to donepezil therapy after discontinuation of memantine monotherapy due to poor tolerability or lack of efficacy. 62 The study reported that re-initiation of donepezil treatment in patients with moderate-to-severe AD showed benefits on cognition measuring an approximate increase of 2 points on MMSE, on global assessment of change measured by CGI-I, and in patient social behavior as rated by a caregiver; but no change in behavior was indicated in NPI scores. Forty-two percent of the patients in this study received before study entrance a long-term therapy with AChEI which was discontinued due to lack of efficacy This implies that in clinical settings, a decision for discontinuation of the treatment might have been done prematurely and that realistic evaluation of treatment benefits should include not only improvement and stabilization but also less-than-expected decline.…”
Section: Clinical Efficacymentioning
confidence: 99%
“…A 12-week, multicenter, open-label study in 103 patients with moderate-to-severe AD focused on switch to donepezil therapy after discontinuation of memantine monotherapy due to poor tolerability or lack of efficacy. 62 The study reported that re-initiation of donepezil treatment in patients with moderate-to-severe AD showed benefits on cognition measuring an approximate increase of 2 points on MMSE, on global assessment of change measured by CGI-I, and in patient social behavior as rated by a caregiver; but no change in behavior was indicated in NPI scores. Forty-two percent of the patients in this study received before study entrance a long-term therapy with AChEI which was discontinued due to lack of efficacy This implies that in clinical settings, a decision for discontinuation of the treatment might have been done prematurely and that realistic evaluation of treatment benefits should include not only improvement and stabilization but also less-than-expected decline.…”
Section: Clinical Efficacymentioning
confidence: 99%
“…Twelve open-label trials were examined based on our search criteria for this meta-analysis. Five studies examined donepezil; [45][46][47][48][49] three, rivastigmine; 46,50,51 two, galantamine; 46,52 one, memantine; 46 one, gabapentin; 53 one, citalopram; 54 one, methylphenidate; 55 and one, atypical antipsychotic. 56 For these studies, average age ranged from 66 to 83 years.…”
Section: Evidence From Open-label Trialsmentioning
confidence: 99%
“…A 12-week, multicenter, open-label study in 103 patients with moderate-to-severe AD focused on switch to donepezil therapy after discontinuation of memantine monotherapy due to poor tolerability or lack of efficacy. 62 The study reported that re-initiation of donepezil treatment in patients with moderate-to-severe AD showed benefits on cognition measuring an approximate increase of 2 points on MMSE, on global assessment of change measured by CGI-I, and in patient social behavior as rated by a caregiver; but no change in behavior was indicated in NPI scores. Forty-two percent of the patients in this study received before study entrance a long-term therapy with AChEI which was discontinued due to lack of efficacy.…”
mentioning
confidence: 99%